State Attorney Law Enforcement in Marriage Annulment and its Contribution to the Development of Family Law in Indonesia - Zaharuddin, Dicky (Universitas Islam Negeri Raden Intan Lampung, 2023)
This articleexamines the optimization of law enforcement by prosecutors in annulling marriages and its contribution to the development of Islamic family law in Indonesia. This research is library research, analyzed by descriptive analysis, which is done by describing the existing facts, the method of analysis used is qualitative method, using Gustav Redbruch's theory of legal objectives. The result of this study is that the optimization of law enforcement by prosecutors in annulling marriage is relevant to Gustav Redbrudh's theory of purpose, that the purpose of law is to provide justice, legal certainty and legal benefits. With the prosecutor being given regulatory rules that support his role in enforcing the law in the field of marriage annulment for someone who violates the legislation, legal justice, legal certainty and legal benefits will be created in the community. The researcher's contribution to the development of family law in Indonesia is in the form of a proposal to policy holders, so that regulations are legislated that specifically regulate the technical guidelines that prosecutors are allowed to act directly in marriage annulment applications.Keyword: Optimization, Law Enforcement, Prosecutor; Marriage Cancellation